MRI bone marrow oedema precedes lumbar bone stress injury diagnosis in junior elite cricket fast bowlers. Issue 19 (October 2019) - Kountouris, Alex; Sims, Kevin; Beakley, David; Saw, Anna E; Orchard, John; Rotstein, Andrew; Cook, Jill L
Abstract : Objectives: Lumbar bone stress injury ('bone stress injury') is common in junior fast bowlers. The repetitive loading of cricket fast bowling may cause bone marrow oedema (BMO), detectable on MRI, before the bowler suffers from symptomatic bone stress injury. We investigated the temporal relationship between BMO, bone stress injury, along with bowling workload correlates, in elite junior fast bowlers throughout a cricket season. Methods: 65 junior fast bowlers were prospectively monitored for one 8-month cricket season. For research purposes, participants had up to six MRI scans at set times in the season; findings were withheld from them and their clinicians. Standard practices for bowling workload monitoring and injury diagnosis were followed. Results: 15 (23%) participants developed bone stress injury during the study. All 15 of these participants had BMO detected on at least one of the preceding MRI scans, including the scan immediately prior to diagnosis. The risk of BMO progressing to bone stress injury during the season was greatest for participants with BMO present 2 weeks prior to the national championship tournament (period of high load) (RR=18.9, OR=44.8). Both bone stress injury and BMO were associated with bowling a higher percentage of days in training and having a shorter bowling break during the season. The number of balls bowled and acute-to-chronic workload were not associated with imaging abnormalities or injury. Conclusion: The presence of BMO on MRI in asymptomatic junior cricket fast bowlers confers a very high risk for bone stress injury. The risk may be managed by MRI screening and monitoring bowling frequency.